Penerapan Bisnis Blue Ocean Strategy Sebagai Inovasi Model Bisnis Dalam Meningkatkan Keunggulan Kompetitif Agrapana Fram - Tian Hardiansyah; Nuraeni; M. Sulhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The agribusiness industry of Indonesia is undergoing a period of substantial growth, characterized by intense competition among producers. This environment has compelled entities such as Agrapana Farm to devise innovative strategies in order to maintain their competitive advantage. Despite the modest level of national milk consumption, demand for dairy products is increasing at a rate that exceeds production, thereby creating opportunities in the market for processed products such as goat milk. Agrapana Farm, established in 2018 in Pandaan, continues to operate using manual methods and encounters challenges in competing in the market. The objective of this research is to analyze Agrapana's innovation strategy using descriptive qualitative methods, through a literature study, observation, and interviews. The collected data underwent a rigorous analysis that entailed the utilization of both SWOT identification and pair-wise comparison weighting techniques. This was followed by the delineation of the organization's strategic position through the application of the Internal-External (IE) matrix. The results indicate that Agrapana is positioned in quadrant V, which suggests the implementation of a strategy focused on the maintenance and enhancement of existing products. In order to successfully navigate the challenges posed by red ocean competition, a blue ocean strategy has been proposed. This strategy involves the innovation of juice fruit skin milk, a product that offers distinct health benefits and added value. This innovation is believed to have the potential to expand the market niche and differentiate Agrapana from competitors.